The relationship between distance-to-default and CDS spreads as measures of default risk for European banks - Kim Ristolainen (Aboa Centre for Economics (ACE), 2015)
CDS spreads are often used as market's view of credit risk. There is no popular alternative to it; perhaps only the distance-to-default measure based on Merton (1974) comes close to it. In this paper we investigate the relationship between these two measures for large European banks in post subprime crises era. The analysis makes use of conventional Granger causality test statistics for individual banks and for the whole panel data. As for the results, we find that the lead-lag relationship between these variables varies over time and over different banks and economic regimes. The lead of distance-to-default is stronger for banks in problem countries (PIGS), during European debt crises, for relatively small banks and when there are large changes in CDS spread. These results suggest that we may have predictive power by not only using the CDS spread, but also other measures such as the distance-to-default.
Keywords: G01; G14; G21; G32; G33; 330; financial stability; European banks; distance-to-default; credit default swap; lead-lag relationship